A defence of Tesman: historiography in Hedda Gabler - Malone, Irina Ruppo (Nordlit, 2015)
The article investigates the subject of history and historiography in Hedda Gabler through a revision of the prevalent view that intended Tesman to be a caricature on the historical profession. Tesman’s research area is innovative; it foreshadows later developments in historical thinking and is therefore linked to Ibsen’s modernism.